Legal Understanding of Partnership between Entrepreneurs and Public Authorities in Russia - I. S. Sushilnikov (Теоретическая и прикладная юриспруденция)
The relevance of the study is due to the unresolved issue of the nature of the partnership between entrepreneurs and authorities, which in practice generates litigations. The article analyzes the use of the term “partnership of entrepreneurs and authorities” in legislation based on methodological prerequisites. The author presents theoretical developments in the ﬁeld of research of the concept of “partnership” in philosophical, economic and legal science. The author attempts to identify the term “partnership of entrepreneurs and authorities”. The local legislation prior to enforcement of law on PPP is considered as taking into account the variety of forms of such partnerships. The author underline the practical signiﬁcance of the term “partnership of entrepreneurs and authorities”. The author gives the deﬁnition of the term “partnership of entrepreneurs and authorities”.